2017
DOI: 10.1080/21645515.2017.1344797
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of Ly6Chi monocytes by multiple GM-CSF injections with HBV vaccine contributes to viral clearance in a HBV mouse model

Abstract: Adjuvants are considered a necessary component for HBV therapeutic vaccines but few are licensed in clinical practice due to concerns about safety or efficiency. In our recent study, we established that a combination protocol of 3-day pretreatments with GM-CSF before a vaccination (3 × GM-CSF+VACCINE) into the same injection site could break immune tolerance and cause over 90% reduction of HBsAg level in the HBsAg transgenic mouse model. Herein, we further investigated the therapeutic potential of the combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 48 publications
0
13
1
Order By: Relevance
“…In contrast to the present study, previous murine experiments have demonstrated that treatment with an adjuvant (e.g. TLR9 ligands) was essential for recruitment of large populations of proinflammatory monocytes into the liver in the context of HBV infection . Following administration of TLR9 ligands, Huang et al .…”
Section: Discussioncontrasting
confidence: 92%
See 3 more Smart Citations
“…In contrast to the present study, previous murine experiments have demonstrated that treatment with an adjuvant (e.g. TLR9 ligands) was essential for recruitment of large populations of proinflammatory monocytes into the liver in the context of HBV infection . Following administration of TLR9 ligands, Huang et al .…”
Section: Discussioncontrasting
confidence: 92%
“…Zhao et al . found similar results following administration of GM‐CSF during DNA vaccination in a murine model of chronic HBV . Interestingly, the requirement for adjuvant administration to drive proinflammatory monocyte recruitment into the liver was not observed in Ccr5 ‐deficient mice.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…This is consistent with the current observation that compared with the control group, the e/c‐null group recruited fewer TNF‐α–producing Ly6C + monocytes and displayed a delayed viral clearance. Second, in an adeno‐associated virus–transduced HBV model, viral clearance by multiple granulocyte‐macrophage colony‐stimulating factor injections is associated with elevated Ly6C + monocytes in peripheral blood mononuclear cells …”
Section: Discussionmentioning
confidence: 99%